2020
DOI: 10.1136/bmjgh-2019-002100
|View full text |Cite
|
Sign up to set email alerts
|

The CURE Protocol: evaluation and external validation of a new public health strategy for treating paediatric hydrocephalus in low-resource settings

Abstract: IntroductionManaging paediatric hydrocephalus with shunt placement is especially risky in resource-limited settings due to risks of infection and delayed life-threatening shunt obstruction. This study evaluated a new evidence-based treatment algorithm to reduce shunt-dependence in this context.MethodsA prospective cohort design was used. The CURE Protocol employs preoperative and intraoperative data to choose between endoscopic treatment and shunt placement. Data were prospectively collected for 730 children i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Systematic coagulation of the choroid plexus was performed to increase the success of ETV as reported in the literature [5]. Our success rate of 47% was adversely affected by the predominance of the youngest age group (1st group, less than 3 months) and by our not shunting those found to have significant cisternal scarring at the time of the ETV, as in the prospective studies from Nigeria and Uganda reported by Lepard et al [4]. Nonetheless, similar to their results, we were able to successfully avoid shunt dependence in nearly half of all infants presenting with hydrocephalus at less than 1 year of age by employing ETV/CPC as the preferred treatment, including all etiologies, those with a cisternal scar, and those under the age of 3 months.…”
Section: Management Of Failed Etv/cpc Proceduresmentioning
confidence: 61%
See 1 more Smart Citation
“…Systematic coagulation of the choroid plexus was performed to increase the success of ETV as reported in the literature [5]. Our success rate of 47% was adversely affected by the predominance of the youngest age group (1st group, less than 3 months) and by our not shunting those found to have significant cisternal scarring at the time of the ETV, as in the prospective studies from Nigeria and Uganda reported by Lepard et al [4]. Nonetheless, similar to their results, we were able to successfully avoid shunt dependence in nearly half of all infants presenting with hydrocephalus at less than 1 year of age by employing ETV/CPC as the preferred treatment, including all etiologies, those with a cisternal scar, and those under the age of 3 months.…”
Section: Management Of Failed Etv/cpc Proceduresmentioning
confidence: 61%
“…A retrospective study analyzed the outcome of hydrocephalus children aged under 12 months old who underwent ETV/CPC between July 2013 and January 2015 in Bamako, Mali, according to the CURE protocol as recently published by Lepard and coauthors (Table 1) [4]. One important difference from their protocol was that a shunt was not automatically placed when a scarred prepontine cistern was encountered at the time of the ETV, but rather, the procedure was given a chance to work.…”
Section: Methodsmentioning
confidence: 99%
“…Egypt, Brazil and Morocco and Uganda are salient examples- Fig. 3 ( Lepard et al., 2020 ). The transition of these nations from recipients to facilitators represents a salient success story for global neurosurgery and an encouragement for more global collaborations between HNRC and LNRC.…”
Section: Discussionmentioning
confidence: 99%
“…Following the success of the Cure International Hydrocephalus Program in Uganda, It has become a reference center for post residency fellowship in pediatric neurosurgery specifically for competency training in Endoscopic Third Ventriculostomy and Choroid Plexus Cauterization around the world. ( Lepard et al., 2020 , Warf, 2005 , Warf and Campbell, 2008 ) In this instance the role of a facilitator represents an upward migration of resource and activity profile. Observation in our model represents a search or readiness to collaborate across profiles of resource strength.…”
Section: Discussionmentioning
confidence: 99%
“…1 A dominant contributor appears to be post-infectious hydrocephalus following neonatal sepsis. 2,3 Surgical treatment of hydrocephalus in this setting has proven to be safe 4 and with a favorable benefit-cost ratio. 5 A recent US National Institutes of Health-funded randomized trial in Uganda has shown that the two available treatment options – ventriculoperitoneal shunt (VPS) 6,7 and the newer endoscopic third ventriculostomy combined with choroid plexus cauterization (ETV/CPC) 813 – are both able to relieve symptoms and allow the brain to grow at 1 year after treatment, often regaining normal size.…”
Section: Introductionmentioning
confidence: 99%